Preparation and Evaluation of Florfenicol Imprinted Polymers by Using Nano-Titanium Dioxide - Ge, Yan-Ru; Huang, Qing; Shao, De-Jia; Qi, Xue-Yong (Asian Journal of Chemistry, 2013)
Surface florfenicol-imprinting technique combined with a sacrificial-support process was established. Taking nano-titanium dioxide as sacrificial carrier and using acrylamide as the functional monomer, the hollow molecularly imprinted polymers (H-MIPs) with specific performances of recognition and adsorption towards to florfenicol were prepared. The microstructures of the molecularly imprinted polymers were characterized by the scanning electron microscopy and energy dispersive X-ray. A series of performance measurement including adsorption kinetics, adsorption isotherm and adsorption selectivity have been studied. In comparison with the polymers synthesized with traditional polymerization method, the results showed that the molecularly imprinted polymers obtained in this study had relatively homogenous structure with numerous mesopores. The results showed that the adsorption approached the equilibrium in 210 min. The research on binding performances of hollow molecularly imprinted polymers demonstrates better specific adsorption ability and selective adsorption to florfenicol. The k' of the hollow molecularly imprinted polymers was nearly 3.95-4.15 times greater than that of the non-imprinted polymer (H-NIPs).